Sex steroid hormones as marker of disease activity in Iraqi women infected with RA - Ahmed T. Enad,; Ban N. AlQadhi, (International Journal of Psychosocial Rehabilitation, 2020)
RA is the autoimmune disease, with a higher prevalence among women, which indicates that female hormonal factors play a role in the disease development. Knowing their effect on the development of RA is clinically important and may contribute to specific preventive strategies in populations at high risk .The aim of this study was to analyze correlation of female hormonal factors with the disease activity of RA..Samples collection of this study was started in October 2018 to January 2019.which included 225 RA women. The patients were divided into two groups depending on menopause status (pre and post menopause).Laboratory tests are included: ACCP, RF, CRP, ESR and hormonal levels of progesterone and Estradiol. The results showed that the percentage of women who had positive results with CCP was 88%,while those with positive RF results was 71% and who with positive CRP was 97%. Most of women diagnosed with rheumatoid arthritis were at the pre-menopausal period 32.5% (73/225) ,while the percentage of the patients women at post-menopause stage were 67.6% (152/225). The results showed that postmenopausal RA women had sever disease activity than premenopausal women and that declared by high levels of both das28 and ESR value (4.63 ± 0.10) and (47.14 ± 0.69) respectively, in comparison to their lower levels (3.66 ± 0.09) and (36.12 ± 0.81) respectively in premenopausal RA women. However, both groups with high levels in comparison to control. A significant negative correlation between BMI and hormones levels in the studied groups, postmenopausal RA women had high BMI (29.71 ± 0.55 kg/m2) than premenopausal women (26.58 ± 0.28 kg/m2) and that characterized by low levels of both progesterone and E2 value (7.24 ± 0.12 ng/ml) and (0.330 ± 0.05 pg/ml) respectively in comparison to their higher levels (42.03 ± 0.59 ng/ml) and (3.49 ± 0.03 pg/ml) respectively in premenopausal RA women. Moreover, both patients groups were had low levels of hormones in comparison to control.Conclusion: The results showed that there were a highly significant negative (p< 0.01) correlation between hormonal levels and RA disease severity (Das28).